Risk Factors for Bronchiolitis in Infants of Hazara Division - A Cross Sectional Study - Shah, Syed Sajid Hussain; Khan, Naima; Khan, Mohsin; Khan, Faiza (Journal of Gandhara Medical and Dental Science, 2022)
OBJECTIVES Bronchiolitis is one of the major causes of hospitalization in the infants. Higher rate of hospitalization and mortality can be reduced by recognizing and control of risk factors for bronchiolitis. The objective of this study is to ascertain risk factors of bronchiolitis in infants, in local population of Hazara Division. METHODOLOGY This cross-sectional study was done in Ayub teaching hospital form January, 2020 till June 2020. Infants of both gender from age of 3 months to 12 months were included with diagnosis of bronchiolitis. Patients with croup, pneumonia, cystic fibrosis and bronchomalasia are excluded. Demographic variables, clinical characteristics and risk factors of bronchiolitis related to infant, mother and family were documented on specific proforma. The data was analyzed by SPSS 21. RESULTS There were 101 infants. Mean age was 5±3.5 months. Male to female ratio was 2.8. 77.2% infant had de livery through surgical procedure and 82% are term. 45% infants were exclusively breast fed. 34% patients room were carpeted, 35% exposed to molds and 81% had history of contact with infected person.28% infants are exposed to passive smoke, 49% had history of allergies and 60% mothers uses perfume to their child’s. 31% infants have more than 10 family members and are living in 2 rooms (p=0.000). Infant weaned at 6month have late onset of bronchiolitis as compare to infants weaned before 6 months (p=0.000). CONCLUSION Perfume/powder use, family history of allergies, history of contact with respiratory infection, delivery with surgical procedure as major new risk factors. Carpets, mold, passive smoking, overcrowding, are also contributing risk factors.